The abusive and the humble: Differential participation in conflicts between the Qollas - Bolton, Ralph (1974)
Aggressiveness and hostility has been the reputation acquired by the Qollas through the years. Anthropologists and other scholars, both foreigners and Peruvians and Bolivians, have emphasized the relevance of this dimension of the Qolla character; and there is no doubt that interpersonal conflict is significantly present in the life of the community. However, we would like to take this opportunity to state that we reject and deplore the sensational and generally erroneous character of the assessments published in certain magazines and newspapers about our previous analyzes of the problem. We will indicate two reservations about Qolla aggressiveness.